Predicting complications in paediatric ulcerative colitis: A longitudinal multicentre cohort study - Claßen, Merle; Schiller, Benjamin; Däbritz, Jan; Buderus, Stephan; Bufler, Philip; Claßen, Martin; Dammann, Söhnke; de Laffolie, Jan; Friedt, Michael; Hauer, Almuthe Christina; Keller, Klaus Michael; Krahl, Andreas; et al. (Alimentary Pharmacology & Therapeutics, 2024)
Background: To prevent complications of paediatric ulcerative colitis (UC), it is critical to understand their predictors. The Paediatric Inflammatory Bowel Disease Ahead (PIBD Ahead) program identified the relevant outcomes and their potential predictors. However, external validation of these results in larger cohorts is required. Aims: The aim of this study is to investigate these outcomes and their predictors. Methods: We included 743 patients aged under 18 years with UC from the multicentre German-Austrian CEDATA-GPGE registry. We performed Cox regressions, Kaplan–Meier estimator, and receiver operating characteristics curve analyses to analyse predictors of poor outcomes. Results: Older age at diagnosis was associated with relapse, hospitalisation, the use of immunomodulators, use of biologics, and therapy escalation. Higher disease activity, as in acute severe colitis in the first 3 months, was significantly associated with further acute severe colitis and the need for biologics. Upper gastrointestinal tract involvement was a risk factor for the need of intravenous corticosteroids and biologics. A faecal calprotectin of >685 μg/g was associated with a higher risk of subsequent acute severe colitis with a sensitivity of 79.0% and a specificity of 59.1%. A lower haematocrit at diagnosis was predictive of the use of biologics. Colectomy was rare. Conclusions: This study validates predictors of poor outcomes in paediatric patients with UC. Our results might help physicians to anticipate poor outcomes and initiate appropriate treatment strategies at an early stage.
CRIS-Team Scopus Importer:2024-09-20